| 16+(-4)-7-
[tex]16 + ( - 4) - 7 = [/tex]

Answers

Answer 1

Answer:

Step-by-step explanation:

16+(-4)-7=16 -(4+7)=16-28 = -12


Related Questions

Which expression will simplify to 1?

Answers

Let us check each Option :

[tex]\mathsf{First\;Option : \left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{m + 9}{m - 9}\right)}[/tex]

[tex]\mathsf{\implies \left(\dfrac{m + 9}{m - 9}\right)^2\;\neq\;1}[/tex]

[tex]\mathsf{Second\;Option : \left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{m - 9}{m + 9}\right)}[/tex]

[tex]\mathsf{\implies 1}[/tex]

[tex]\mathsf{Third\;Option : \left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{9 + m}{9 - m}\right)}[/tex]

[tex]\mathsf{\implies \left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{m + 9}{-(m - 9)}\right)}[/tex]

[tex]\mathsf{\implies-\left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{m + 9}{m - 9}\right)}[/tex]

[tex]\mathsf{\implies-\left(\dfrac{m + 9}{m - 9}\right)^2\;\neq\;1}[/tex]

[tex]\mathsf{Fourth\;Option : \left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{9 - m}{9 + m}\right)}[/tex]

[tex]\mathsf{\implies \left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{-(m - 9)}{9 + m}\right)}[/tex]

[tex]\mathsf{\implies -\left(\dfrac{m + 9}{m - 9}\right)\left(\dfrac{m - 9}{9 + m}\right)}[/tex]

[tex]\mathsf{\implies -1\;\neq\;1}[/tex]

Answer : Option (2)

Answer:

B.⁽[tex](\frac{m}{m}\frac{+9}{-9} ) (\frac{m}{m} \frac{- 9}{+ 9} )[/tex]

Step-by-step explanation:

The graph of relation r is shown. Which of the following graphs represents the relation and it’s inverse

Answers

Answer:

To easily solve this question, we must realize that the graph of the relation is very similar to that of the expression

y = √(x-a) , where a>0

If we take a look at the image attached, we have plotted the graph of

y = √(x-1) , and its correspondent inverse function.

This means that the answer is the first option

algebra II engenuity

Answers

Answer:

First Option

Step-by-step explanation:

Given expression is:

[tex]\sqrt[4]{x^{10}}[/tex]

The radicand's exponent will be made multiple of 4 to make the calculations easy

So,

[tex]= \sqrt[4]{x^8 * x^2}[/tex]

The 4 outside the radical means that the power that will be multiplied with the exponents will be 1/4

So,

[tex]= x^{(8*\frac{1}{4})} * x^{(2*\frac{1}{4})}\\=x^2 \sqrt[4]{x^2}[/tex]

As x^2 couldn't be solved using radical, it will remain inside the radical.

So the correct answer is first option..

Answer: First option.

Step-by-step explanation:

Knwing that we must find which is the equivalent expression of the expression [tex]\sqrt[4]{x^{10}}[/tex], it is important to remember the Product of powers property, which states the following:

[tex](a^m)(a^n)=a^{(m+n)}[/tex]

The we can rewrite the expression:

 [tex]=\sqrt[4]{x^8x^2}[/tex]

Remember that:

[tex]\sqrt[n]{a^n}=a[/tex]

Then we get this equivalent expression:

 [tex]=x^2(\sqrt[4]{x^2})[/tex]

what is the solution set of 7x^2 + 3x = 0

Answers

Answer:

the answer is x=0,-(3/7)

Step-by-step explanation:

Answer:

x = { - [tex]\frac{3}{7}[/tex], 0 }

Step-by-step explanation:

Given

7x² + 3x = 0 ← factor out x from each term

x(7x + 3) = 0

Equate each factor to zero and solve for x

x = 0

7x + 3 = 0 ⇒ 7x = - 3 ⇒ x = - [tex]\frac{3}{7}[/tex]

Classify the following triangle check all that apply

Answers

Answer: B and F

Hope it helps!!!

Answer: OPTION B AND OPTION D.

Step-by-step explanation:

Analyze  the triangle provided.

You can observe that the lenghts of its sides are: 10.9, 15, 14

Then the lenghts of its sides are not equal.

 By definition, when all sides of a triangle are different this is called: "Scalene".

You can notice that the measures of its angles are: 63°, 44° and 73°

Then, all its angles are less than 90 degrees.

By definition if all three angles of a triangle are less than 90 degrees, then is called: "Acute".

Judy works at a candy factory that makes Sugar Rush candy bars. She is in charge of quality control and has to make sure each candy bar has the correct mass. Each candy bar is required to weigh 12 grams, with a tolerance of 0.45 grams. What is the acceptable weight range for each candy bar?

1. Define a variable for this situation.
2. Write the absolute value inequality that describes the acceptable weight range for each candy bar.
3.Solve the absolute value inequality to find the acceptable weight range for each candy bar using numbers and symbols.
4. Using words, describe the possible acceptable weight range for each candy bar.

Answers

Step-by-step explanation:

1. x = acceptable weight of candy bar

2. |x - 12| ≤ 0.45

3. x - 12 ≤ 0.45, x - 12 ≥ -0.45

x ≤ 12.45, x ≥ 11.55

4. The acceptable weight range for each candy bar is between 11.55 grams and 12.45 grams.

On which number line are -3 and its opposite shown?

Answers

Answer:

The number line should look like this;

<---- -3 -------- 0 ------- 3 ----->

It must have both 3 and -3 shown

Step-by-step explanation:

Answer:the possittive is to the right of the 0 and the negative is to  the left .

Step-by-step explanation:how do you feguire this out because the left of a number line is always negative and the right is always posittive easy right i hope it helped you just like when i learned it it helped me.

Which is correct? I am marking Brainliest.

Answers

Answer:

A. concave hexagon

Step-by-step explanation:

It has 6 sides, so it's a hexagon. (A heptagon has 7 sides.)

If all interior angles are less than 180 deg, then it is convex. There is one interior angle on the left side that is more than 180 deg, so it is concave.

Answer: concave hexagon

hello! i’m currently working on some practice questions, and i was wondering how you would solve this expression!

Answers

Answer:

7

Step-by-step explanation:

Givens

x = 4

y = 2

z =-3

equation

xy - z^y

Solution

(4)(2) - (-3)^2     be sure and add the brackets. Otherwise it won't come out correctly.

16 - (9) = 7

Which congruence theorems prove tht
MNP and QRS are be congruent?
Word Bank:
AAS theorem, ASA postulate, SAS postulate,
SSS postulate, HA, AA, HL, LA, LL, HH

Answers

Answer

AAS

Step-by-step explanation:

What is the solution of the graph?

Answers

Answer:

no solution

Step-by-step explanation:

The solution to a system of equations given graphically is at the point of intersection of the 2 graphs.

The given lines are parallel ( both have a slope = 2 )

Hence the lines never intersect thus there is no solution.

A sequence is defined by the recursive function
f(n + 1) = f(n) - 2
if f(1) = 10, what is f(3)?
1
6
8
30

Answers

Answer:

6

Step-by-step explanation:

[tex]f(n+1)=f(n)-2\\\\f(1)=10\\f(2)=f(1)-2=10-2=8\\f(3)=f(2)-2=8-2=6[/tex]

Answer:

B) 6

Step-by-step explanation:

Three families went to the movies together. The Smiths ordered two tubs of popcorn, one plate of nachos, and three drinks. They spent $65. The Langes ordered three tubs of popcorn, two plates of nachos, and five drinks. They spent $85. The Radfords ordered one tub of popcorn, one plate of nachos, and two drinks. They spent $40. Which system of equations matches their night at the movies?

Answers

Answer:

2t + n + 3d = 65

3t + 2n + 5d = 85

t + n + td = 40

Step-by-step explanation:

tubs of popcorn = t

plates of nachos = n

drinks = d

The Smiths: 2t + n + 3d = 65

The Langes: 3t + 2n + 5d = 85

The Radfords: t + n + td = 40

So, the correct answer would be the one including all 3 of these equations. :)

Answer:

The system of equations are:

[tex]2t + n + 3d = 65[/tex]

[tex]3t + 2n + 5d = 85[/tex]

[tex]t + n + 2d = 40[/tex]

Step-by-step explanation:

Consider the provided information.

let "t" represents tubes of popcorn, "n" represents nachos and "d" represents drink.

The Smiths ordered two tubs of popcorn, one plate of nachos, and three drinks. They spent $65. Which can be represents as:

[tex]2t + n + 3d = 65[/tex]

Langes ordered three tubs of popcorn, two plates of nachos, and five drinks. They spent $85. Which can be represents as:

[tex]3t + 2n + 5d = 85[/tex]

The Radfords ordered one tub of popcorn, one plate of nachos, and two drinks. They spent $40. Which can be represents as:

[tex]t + n + 2d = 40[/tex]

Thus, the system of equations are:

[tex]2t + n + 3d = 65[/tex]

[tex]3t + 2n + 5d = 85[/tex]

[tex]t + n + 2d = 40[/tex]

Your phone plan charges you an initial fee and then a certain amount depending on the amount of data you use they send you periodic updates of your insiste and your current bill cost. After using 3 GB of data you owe $30. After 5 GB of data you owe $40. What is the initial fee prior to the data usage charge ?

Answers

Answer:

5

Step-by-step explanation:

dot

If there are 6 serving in a 2/3 pound lb package of pound is in each serving

Answers

Answer:

[tex]\boxed{\math{\frac{1}{9}\text{ lb}}}[/tex]

Step-by-step explanation:

[tex]\text{Size of one serving} = \dfrac{\text{Total size}}{\text{No of servings}} = \dfrac{\frac{2}{3}\text{ lb}}{\text{6 servings}}\\\\\text{Change the 6 to a fraction and change divide to multiply}\\\\\dfrac{2}{3} \div 6 = \dfrac{2}{3} \times \dfrac{1}{6}[/tex]

[tex]\text{Cancel the 2s}\\\\\dfrac{2}{3} \times \dfrac{1}{6} = \dfrac{1}{3} \times \dfrac{1}{3}\\\\\text{Multiply numerators and denominators}\\\\\dfrac{1}{3} \times \dfrac{1}{3} = \dfrac{1}{9}\\\\\text{Each serving contains }\boxed{\mathbf{\frac{1}{9}\textbf{ lb}}}[/tex]

The area of a compact disc is 452 4/7 square centimeters. What is the diameter of a compact disc ? Use 22/7 as an approximation for pie?

Answers

[tex]\bf \textit{area of a circle}\\\\ A=\pi r^2~~ \begin{cases} r=radius\\ \cline{1-1} A=452\frac{4}{7} \end{cases}\implies 452\frac{4}{7}=\pi r^2\implies \cfrac{3168}{7}=\pi r^2 \implies \cfrac{3168}{7\pi }=r^2 \\\\\\ \stackrel{\pi =\frac{22}{7}}{\cfrac{3168}{7\cdot \frac{22}{7}}}=r^2\implies \cfrac{3168}{22}=r^2\implies 144=r^2\implies \sqrt{144}=r\implies 12=r \\\\[-0.35em] \rule{34em}{0.25pt}\\\\ ~\hfill \stackrel{diameter=2r}{d=24}~\hfill[/tex]

Can someone help me plz and the last two that you couldn’t see was ( c- 1 1/3 ) and ( D- 1 1/9)

Answers

Answer:

B 9/10

Step-by-step explanation:

3/5 ÷2/3

Copy dot flip

3/5 * 3/2

9/10

cos^2x+cos^2(120°+x)+cos^2(120°-x)
i need this asap. pls help me​

Answers

Answer:

[tex]\frac{3}{2}[/tex]

Step-by-step explanation:

Using the addition formulae for cosine

cos(x ± y) = cosxcosy ∓ sinxsiny

---------------------------------------------------------------

cos(120 + x) = cos120cosx - sin120sinx

                   = - cos60cosx - sin60sinx

                   = - [tex]\frac{1}{2}[/tex] cosx - [tex]\frac{\sqrt{3} }{2}[/tex] sinx

squaring to obtain cos² (120 + x)

= [tex]\frac{1}{4}[/tex]cos²x + [tex]\frac{\sqrt{3} }{2}[/tex]sinxcosx + [tex]\frac{3}{4}[/tex]sin²x

--------------------------------------------------------------------

cos(120 - x) = cos120cosx + sin120sinx

                   = -cos60cosx + sin60sinx

                   = - [tex]\frac{1}{2}[/tex]cosx + [tex]\frac{\sqrt{3} }{2}[/tex]sinx

squaring to obtain cos²(120 - x)

= [tex]\frac{1}{4}[/tex]cos²x - [tex]\frac{\sqrt{3} }{2}[/tex]sinxcosx + [tex]\frac{3}{4}[/tex]sin²x

--------------------------------------------------------------------------

Putting it all together

cos²x + [tex]\frac{1}{4}[/tex]cos²x + [tex]\frac{\sqrt{3} }{2}[/tex]sinxcosx + [tex]\frac{3}{4}[/tex]sin²x + [tex]\frac{1}{4}[/tex]cos²x - [tex]\frac{\sqrt{3} }{2}[/tex]sinxcosx + [tex]\frac{3}{4}[/tex]sin²x

= cos²x + [tex]\frac{1}{2}[/tex]cos²x + [tex]\frac{3}{2}[/tex]sin²x

= [tex]\frac{3}{2}[/tex]cos²x + [tex]\frac{3}{2}[/tex]sin²x

= [tex]\frac{3}{2}[/tex](cos²x + sin²x) = [tex]\frac{3}{2}[/tex]

                 

66=1/2 h(5+6)
Solve for h

Answers

Answer:

h= 12

Step-by-step explanation:

Given

66 = [tex]\frac{1}{2}[/tex] h(5 + 6)

Multiply both sides by 2 to eliminate the fraction

132 = h(5 + 6)

132 = 11h ( divide both sides by 11 )

12 = h

Simplify the expression.
(7.46)** . (7.46)

Answers

Answer:

D. 7.46  

Hope this helps and have a nice day!!

If I'm wrong pleaseeee tell me

Step-by-step explanation:

Consider the paragraph proof.

Given: D is the midpoint of AB, and E is the midpoint of AC.
Prove:DE = BC



It is given that D is the midpoint of AB and E is the midpoint of AC. To prove that DE is half the length of BC, the distance formula, d = , can be used to determine the lengths of the two segments. The length of BC can be determined with the equation BC = , which simplifies to 2a. The length of DE can be determined with the equation DE = , which simplifies to ________. Therefore, BC is twice DE, and DE is half BC.

Which is the missing information in the proof?

a
4a
a2
4a2

Answers

Answer:

a

Step-by-step explanation:

You're trying to find the distance between D and E so u use the distance formula.

sqrt (a+b-b^2)+(c-c)^2=sqrt a^2=a

Answer:

a

Step-by-step explanation:

We are given that

D is the mid-point of AB and E is the mid-point of AC.

We have to find the missing information in given proof of DE is equal to half of BC.

Proof:

D is the mid-point of AB and E is the mid-point of AC.

The coordinates of A are (2b,2c)

The coordinates of D are (b,c)

The coordinates of E are (a+b,c)

The coordinates of  B are (0,0)

The coordinates of  C are (2a,0)

Distance formula:[tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]

Using the formula

Length of BC=[tex]\sqrt{(2a)^2+(0-0)^2}=2a[/tex] units

Length of DE=[tex]\sqrt{(a+b-b)^2+(c-c)^2}=a[/tex] units

[tex]BC=2a=2\times DE[/tex]

[tex]DE=\frac{1}{2}BC[/tex]

Hence, proved.

Option A is true.

What is the greatest common factor of 22a2 and 32a

Answers

Step-by-step explanation:

Write the prime factorization for each:

22a² = 2×11×a²

32a = 2⁵×a

So the greatest common factor is 2a.

Explain how you can use equivalent fractions to find the quotient of 2 3 ÷ 4.

Answers

Answer:

see below

Step-by-step explanation:

2/3 ÷ 4

We use copy dot flip

The flip means make a reciprocal of the second number

2/3 * 1/4

Multiply the numerators

2*1 = 2

Multiply the denominators

3*4 =12

Put the numerator over the denominator

2/12

Simplify

1/6

To use equivalent fractions to find the quotient of \( \frac{2}{3} \) ÷ 4, follow these steps:

### Step 1: Understand the Operation
Division of fractions can be thought of as multiplying by the reciprocal. The reciprocal of a number a is simply \( \frac{1}{a} \).

### Step 2: Find the Reciprocal of the Divisor
The divisor here is the whole number 4. Its reciprocal is \( \frac{1}{4} \).

### Step 3: Multiply the Dividend by the Reciprocal of the Divisor
Instead of dividing \( \frac{2}{3} \) by 4, you can multiply \( \frac{2}{3} \) by \( \frac{1}{4} \).

### Step 4: Perform the Multiplication
Now, multiply the two fractions:

\[ \frac{2}{3} \times \frac{1}{4} = \frac{2 \cdot 1}{3 \cdot 4} \]

This results in a new fraction:

\[ \frac{2}{12} \]

### Step 5: Simplify the Resulting Fraction
Finally, you need to simplify the fraction to its simplest form. To do that, find the greatest common factor (GCF) of the numerator and the denominator and divide both by this number.

For \( \frac{2}{12} \), the greatest common factor is 2. So we divide both the numerator and the denominator by 2:

\[ \frac{2 \div 2}{12 \div 2} = \frac{1}{6} \]

### Conclusion
Therefore, the quotient of \( \frac{2}{3} \) ÷ 4 is \( \frac{1}{6} \). This is the simplest form of the fraction you obtain when \( \frac{2}{3} \) is divided by 4.

I need help finding the answer

Answers

Answer:

32

Step-by-step explanation:

The formula is base x hight.

The base is 8.

The hight is 4.

You just multiply the two.

8x4=32

Simple. :)

Hope this helps!

Answer: 42 inches squared

Step-by-step explanation:

To find the total area you will find the area of the rectangle and then add that to the area of the triangle. (Remember a triangle is half of a rectangle!) First we will find the area of the rectangle...

4x8=32 inches squares

Now let’s find the area of the triangle, find the rectangle then divide it in half...

5x4=20 inches squared

20/2=10 inches squared

Now add 32 to 10 and you’ll have your answer!

32+10=42 inches squared

y+1=-3x(x+4)
help me solve please

Answers

y+1 = -3x^2 - 12x

Y= -3x^2 -12x -1

Hope this helps!

Simplify 3(2x - 5).for me please

Answers

Answer:

6x-15

Step-by-step explanation:

3*2x= 6x

3*5=15

6x-15

Answer:

6x - 15

Step-by-step explanation:

3(2x - 5)

Distributive property

= 3(2x) + (3)(-5)

= 6x - 15

Divide simplify your answer

Answers

Answer:

[tex]\large\boxed{\dfrac{2s-6}{s+3}}[/tex]

Step-by-step explanation:

[tex]s^2-9=s^2-3^2\qquad\text{use}\ a^2-b^2=(a-b)(a+b)\\=(s-3)(s+3)\\\\s^2+6s+9=s^2+2(s)(3)+3^2\qquad\text{use}\ (a+b)^2=a^2+2ab+b^2\\=(s+3)^2[/tex]

[tex]\dfrac{s^2-9}{2s}\div\dfrac{s^2+6s+9}{4s}=\dfrac{s^2-9}{2s\!\!\!\!\diagup_1}\cdot\dfrac{4s}{s^2+6s+9}\\\\=\dfrac{(s-3)(s+3)}{2s\!\!\!\!\!\diagup_{_1}}\cdot\dfrac{4s\!\!\!\!\!\diagup^{^2}}{(s+3)^2}=\dfrac{2(s-3)(s+3)}{(s+3)(s+3)}\qquad\text{cancel}\ (s+3)\\\\=\dfrac{2(s-3)}{s+3}=\dfrac{2s-6}{s+3}[/tex]

what is the eighth term in the sequence x+3, - 2x^2 - 6x, 4x^3 +12x^2​

Answers

Answer:

[tex]a_8=-128x^8-384x^7[/tex]

Step-by-step explanation:

The terms of the sequence are:

[tex]x+3,-2x^2-6x,4x^3+12x^2,...[/tex]

We can rewrite the terms in factored form to get;

[tex]x+3,-2x(x+3),4x^2(x+3),...[/tex]

We can see that the subsequent terms are obtained by multiplying the previous term by [tex]-2x[/tex]. This is called the common ratio.

Therefore the first term of this geometric sequence is [tex]a_1=x+3[/tex] and the common ratio is [tex]r=-2x[/tex].

The nth term of a geometric sequence is given by: [tex]a_n=a_1(r^{n-1})[/tex].

Let us substitute the first term, the common ratio, and [tex]n=8[/tex] to obtain:

[tex]a_8=(x+3)(-2x)^{8-1}[/tex]

[tex]a_8=(x+3)(-2x)^{7}[/tex]

[tex]a_8=-128x^7(x+3)[/tex]

[tex]a_8=-128x^8-384x^7[/tex]

What is the value of p in the equation y^ = -4x?

Answers

ANSWER

p=-1

EXPLANATION

The given equation is

[tex] {y}^{2} = - 4x[/tex]

We compare with the general equation of the parabola with vertex at the origin.

[tex]{y}^{2} =4px[/tex]

Comparing the right hand side we have,

[tex]4px = - 4x[/tex]

Divide both sides by 4x

[tex] \frac{4px}{4x} = \frac{ - 4x}{4x} [/tex]

This implies that,

[tex]p = - 1[/tex]

6x - 26 = 58 + 4x, 15 points to whoever solves this

Answers

Answer:

x=42

Step-by-step explanation:

Add by 26 from both sides of equation.

6x-26+26=58+4x+26

Simplify.

6x=4x+84

Subtract by 4x from both sides of equation.

6x-4x=4x+84-4x

Simplify.

2x=84

Divide by 2 from both sides of equation.

2x/2=84/2

Simplify, to find the answer.

84/2=42

x=42 is the correct answer.

I hope this helps you, and have a wonderful day!

Other Questions
The first ferris wheel was 250 feet in diameter. It was invented by John Ferris in 1893. Assuming it made one revolution every 30 seconds, what was the linear speed of a passenger ( assuming the passenger is on the edge of the ferris wheel) in feet per minute. (30 POINTS....AP PSYCH URGENT)Maria and Lisa are part of a group at the local high school that is trying to end the cliquishness in the high school that has led to fights after school. Explain how what each of the following terms might contribute to the situation.prejudicein-groupsocial normsscapegoatingequal status contactattribution theory Three runners competed in a race. Data were collected at each mile mark for each runner. If the runner ran at a constant pace, the data would be linear. A regression line fitted to their data. Uses the residual plots to decide which data set is best fit by the regression line, and then identify the runner that kept the most consistent pace. Solve for x: 2/x-2+7/x2-4=5/x What structural technique does the writer use in this passage? the segments shown below could form a triangle How to slove the equation 6.8x+9.3=-9.4+3.4(2-5x) Explain five different ways that you can respond to global warming. Islam kltr ve medeniyeti islam ehirlerinde caminin merkez olmasinin kisaca nedeni LINDA Hola, Juan. (1) [tomar] tres clases: qumica, biologa y computacin. Y t, cuntas clases (2) [tomar]? JUAN (3) [tomar] cuatro: sociologa, biologa, arte y literatura. Yo (4) [tomar] biologa a las cuatro. Y t? LINDA Lily, Alberto y yo (5) [tomar] biologa a las diez. JUAN (6) [estudiar] ustedes mucho? LINDA S, porque (because) hay muchos exmenes. Alberto y yo (7) [estudiar] dos horas juntos todos los das (together every day). JUAN Lily no (8) [estudiar] con ustedes? LINDA No, ella (9) [estudiar] con su novio (boyfriend), Arturo. Which absolute value inequality represents the given graph?A. 18x + 91 < 57B. 18x + 91 > 57C. 18x +91 557D. 18x +9 57 which of these is associated with bulimia nervosaa.being at least 30 percent underweight b. bingeing and purging c. bingeing but not purging d. bingeing at least 30 percent overweight What was the effect and importance of Great Britains promise of freedom to slaves who joined the British side? A teacher modeled part of a DNA molecule using two of these coiled springs. Which part of the DNA molecule was the teacher most likely modeling? What is the circumference of circle P?Express your answer in terms of .AB = 14 in. Write four to six sentences explaining the use of extended metaphor in the poem caged bird by maya angelou. Which represents a negative impact of technology?OA. Increased recyclingOB. Renewable energy sourcesOC. Higher food productionOD. Climate change Which shows the factored form of x2-12x-45? when studying atoms, scientists can ignore the blank force Which statement best describes why carbon can form a wide variety of organic compounds? Each carbon atom ionically bonds with atoms of carbon, hydrogen, oxygen, and nitrogen. Each carbon atom covalently bonds with atoms of carbon, hydrogen, oxygen, and nitrogen. Each carbon atom ionically bonds with atoms of oxygen and nitrogen. Each carbon atom covalently bonds with atoms of oxygen and nitrogen.